2012
DOI: 10.1002/aic.13882
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production via solar‐aided water splitting thermochemical cycles with nickel ferrite: Experiments and modeling

Abstract: Water splitting -thermal reduction cyclic studies with NiFe 2 O 4 redox materials were performed in a differential fixed-bed laboratory reactor in the temperature range 700-1,400C to quantify the effects of operation temperatures and steam mole fraction on hydrogen and oxygen yields. Hydrogen yield increased drastically by an increase of the water splitting temperature from 800 to 1,000 C reaching a plateau at 1,100 C. In parallel, a simple mathematical model was formulated describing the water splitting proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…8 However, NiFe 2 O 4 nanoparticles are found to have the mixed spinel structure together with the inverse one, [9][10][11] i.e., some Ni 2+ ions may occupy the T d sites. NiFe 2 O 4 has an inverse spinel structure with Ni 2+ ions on octahedral B sites (denoted as O h -sites) and Fe 3+ ions distributed on both the tetrahedral A (denoted as T dsite) and the O h -sites equally.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, NiFe 2 O 4 nanoparticles are found to have the mixed spinel structure together with the inverse one, [9][10][11] i.e., some Ni 2+ ions may occupy the T d sites. NiFe 2 O 4 has an inverse spinel structure with Ni 2+ ions on octahedral B sites (denoted as O h -sites) and Fe 3+ ions distributed on both the tetrahedral A (denoted as T dsite) and the O h -sites equally.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that partial substitution of iron in the magnetite phase by Mn, Ni, or Zn forms mixed-metal oxides of the type MFe 2 O 4 (mixed ferrites) that are more reducible and require moderate, upper (thermal reduction) operating temperatures. A whole series of such ferrites has been tested experimentally and studied thermodynamically, including either only one divalent metal cation in the M site, such as MnFe 2 O 4 (Tamaura et al, 1999), ZnFe 2 O 4 (Aoki, Kaneko, et al, 2004;Kaneko et al, 2004), NiFe 2 O 4 (Agrafiotis, Zygogianni, Pagkoura, Kostoglou, & Konstandopoulos, 2013;Fresno, Yoshida, Gokon, FernandezSaavedra, & Kodama, 2010;Gokon, Takahashi, Yamamoto, & Kodama, 2008;Gokon, Mataga, Kondo, & Kodama, 2011), or CoFe 2 O 4 (Miller et al, 2008), or two such cations-i.e., of the type (C x D 1-x ) þ2 Fe 2 þ3 O 4 -including Ni 0.5 Mn 0.5 Fe 2 O 4 (Tamaura et al, 1998;Tamaura, Steinfeld, Kuhn, & Ehrensberger, 1995), Mn 0.5 Zn 0.5 Fe 2 O 4 (Inoue et al, 2004), and other cation stoichiometries (Allendorf, 2008;Kodama & Gokon, 2007;Kojima et al, 1996;Miller et al, 2006). However, their thermal reduction temperatures are still high (z1600e1700 K), which is an important drawback because it can cause significant sintering of the metal oxide.…”
Section: The Ferrite Cyclementioning
confidence: 99%
“…Various ferrite powders synthesis techniques have been pursued from solid, liquid or gaseous precursors, among others co-precipitation [95], aerial oxidation of aqueous suspensions of Fe(II) hydroxide [96,97], sol-gel [98], atomic layer deposition [99,100], combustion synthesis [86,101] and spray pyrolysis [102]. Comparative testing of ferrite powders has identified the temperature ranges recommended for cyclic operation as well as the effects of process parameters on H 2 /O 2 yields [86,89,103]. Their TR temperatures are still high (E 1600-1700 K)-an important drawback since it can cause significant sintering of the oxide.…”
Section: The Ferrites' Cyclementioning
confidence: 99%